Analisis Manajemen Rumah Potong Hewan Bangkinang Kabupaten Kampar dan Dampaknya Terhadap Lingkungan - Yudhi Ardianto; Yusmarini Yusmarini; Ridwan Manda Putra (Pelantar Press, 2025)
The Slaughterhouse (RPH) plays a vital role in supporting food security and the regional economy. However, if not properly managed, it can have significant environmental impacts. This study aims to analyze the management of the Bangkinang Slaughterhouse in Kampar Regency and evaluate its environmental impact. The methods used include field surveys, observations, interviews with relevant stakeholders, and wastewater quality analysis using the grab sampling method. The results show that while the management of the Bangkinang Slaughterhouse complies with most of the requirements of the Minister of Agriculture Regulation No. 13/Permentan/OT.140/1/2010, the Wastewater Treatment Plant (IPAL) facilities are not functioning optimally. Measurements of wastewater quality revealed that COD and BOD levels exceed the allowable thresholds, posing a risk of environmental pollution. This condition requires improvements in waste management to prevent negative impacts on the ecosystem. Furthermore, public perception of the slaughterhouse tends to be negative due to the limited social benefits, although negative effects such as odor and health disturbances are still within a non-disruptive category. This study recommends the optimization of the IPAL system and enhancement of supporting facilities to ensure better and more environmentally friendly waste management